2014
DOI: 10.1371/journal.pone.0097787
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Studies Suggest a Possible Involvement of HPV Infection in the Early Stage of Breast Carcinogenesis via APOBEC3B Induction

Abstract: High prevalence of infection with high-risk human papilloma virus (HPV) ranging from 25 to 100% (average 31%) was observed in breast cancer (BC) patients in Singapore using novel DNA chip technology. Early stage of BC demonstrated higher HPV positivity, and BC positive for estrogen receptor (ER) showed significantly higher HPV infection rate. This unique association of HPV with BC in vivo prompted us to investigate a possible involvement of HPV in early stages of breast carcinogenesis. Using normal breast epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 52 publications
(60 reference statements)
7
83
1
4
Order By: Relevance
“…1A). Previous studies reported that A3B expression was upregulated by HBV16 E6/E7 Ohba et al, 2014;Vieira et al, 2014). However, the HPV16-positive specimen used in this study expressed low levels of A3B (Fig.…”
Section: Expression Of Apobec3s In Healthy and Hpv16-positive Cervicamentioning
confidence: 48%
“…1A). Previous studies reported that A3B expression was upregulated by HBV16 E6/E7 Ohba et al, 2014;Vieira et al, 2014). However, the HPV16-positive specimen used in this study expressed low levels of A3B (Fig.…”
Section: Expression Of Apobec3s In Healthy and Hpv16-positive Cervicamentioning
confidence: 48%
“…B-Myb has been implicated in a positive regulatory role for Cdk1 expression (49,56). We and others have shown that E7 upregulates B-Myb expression (7,46). Moreover, downregulation of B-Myb-induced G 1 arrest in E7-expressing cells upon DNA damage has been described previously (59).…”
Section: Gene Expression Profiling Of Hpv-16 E7-expressing Cellsmentioning
confidence: 62%
“…Among these genes, the APOBEC-3B gene, a member of the cytidine deaminase gene family, is activated by HPV infection and increases genome instability (46). The nuclear protein DEK has shown to be upregulated in E7-expressing cells as well as cervical intraepithelial neoplasia (CIN) and cervical cancers.…”
Section: Gene Expression Profiling Of Hpv-16 E7-expressing Cellsmentioning
confidence: 99%
“…Ohba et al showed that HPV E6 and E7 individually activate the A3B promoter and the E6/E7-induced DNA double-stranded breaks are abolished by A3B knockdown [7]. This suggests that the mutagenic activities of E6/E7 are attributable to the induction of A3B expression.…”
Section: Introductonmentioning
confidence: 99%